Deplorable Distortions on Social Media regarding Covid-19 and Social Anxiety among Indian Adults - JAVED, RUQAIYA; TAWFEEQ ALEE, NONGZAIMAYUM; HASAN, ASIF (International Journal of Psychosocial Rehabilitation, 2020)
Erroneous news or distorted information and half-cooked theories circulating in social media is a big nuisance nowadays everywhere in the world that shapes suspicion among communities, communal feelings and irrational behaviour. This study aims to identify a relationship between such deplorable, twisted fake information spreading on social media platforms and different social anxieties of the young adults who are exposed to it at this time of COVID-19 pandemic. The study comprised of Indian adults (N= 562) selected randomly from different districts across the country. Social media disinformation survey (SMDS) questionnaire and social anxiety scale for social media users (SAS-SMU) were used and the results of correlation showed a positive and significant correlation between social media disinformation spread and social anxieties. The CFA results confirms the four-factor structure measurement model of SAS-SMU on Indian sample. Also, the two-factor structure of SMDS represents a good model fit to the data specifying the indicator variables measures the theoretical construct social media disinformation. Furthermore, the results of two-way MANOVA yielded a statistically significant interaction effect between social media platforms and covid-19 rumour awareness on the social media disinformation and all four social anxieties.